Devising an integrated method for evaluating the efficiency of scrum-based projects in the field of information technology - Prokopenko, Tatiana; Lavdanska, Olha; Povolotskyi, Yaroslav; Obodovskyi, Bohdan; Tarasenko, Yaroslav (Eastern-European Journal of Enterprise Technologies, 2021)
An integrated method for evaluating the effectiveness of projects in the field of information technology has been proposed, which could ensure effective management decision-making. All features inherent in the implementation of the Scrum methodology used in the management of information technology projects have been taken into consideration. Ambiguous situations that constantly arise during the implementation of projects affect their effectiveness. Therefore, constant monitoring of the project efficiency would provide opportunities for the project manager to make management decisions promptly, which could contribute to improving the efficiency of the project. The integrated method for evaluating the effectiveness of projects was devised in the class of organizational-technological systems based on the combined use of formalized, intelligent, and expert methods. The results of applying a given method include an increase in the project efficiency by 1.52 % by complying with time limits, a reduction in the overspending of financial resources and losses during the project, as well as the improved productivity of teamwork. A model of the project efficiency index has been devised, which would ensure taking into consideration the peculiarities of the organizational and technological components of the project, as well as establishing a logical connection between the criteria that characterize the organizational component of the project, on the one hand, and the project-technological component, on the other. The resulting project efficiency index contributes to further research of various alternative scenarios for the project implementation and forecasts the dynamics of achieving strategic goals, as well as the dynamics of process implementation. The proposed procedure for evaluating the effectiveness of the project under Scrum conditions could become the basis of the information technology of project management and the appropriate decision support system